Translation Inhibitors Induce Formation of Cholesterol Ester-Rich Lipid Droplets - Suzuki, Michitaka (Public Library of Science, 2012)
Lipid droplets (LDs) in non-adipocytes contain triglycerides (TG) and cholesterol esters (CE) in variable ratios. TG-rich LDs are generated when unsaturated fatty acids are administered, but the conditions that induce CE-rich LD formation are less well characterized. In the present study, we found that protein translation inhibitors such as cycloheximide (CHX) induced generation of CE-rich LDs and that TIP47 (perilipin 3) was recruited to the LDs, although the expression of this protein was reduced drastically. Electron microscopy revealed that LDs formed in CHX-treated cells possess a distinct electron-dense rim that is not found in TG-rich LDs, whose formation is induced by oleic acid. CHX treatment caused upregulation of mTORC1, but the CHX-induced increase in CE-rich LDs occurred even when rapamycin or Torin1 was given along with CHX. Moreover, the increase in CE was seen in both wild-type and autophagy-deficient Atg5-null mouse embryonic fibroblasts, indicating that mTORC1 activation and suppression of autophagy are not necessary to induce the observed phenomenon. The results showed that translation inhibitors cause a significant change in the lipid ester composition of LDs by a mechanism independent of mTORC1 signaling and autophagy.